Высокоскоростной широкополосный спутниковый интернет и области его применения - Мамедов, Эльнур; Искендеров, Фуад; Чаллари, Энрики (My University, 2024)
In this dissertation, a comprehensive research study was conducted on the analysis and modeling of high-speed broadband satellite internet systems using low-Earth orbit (LEO) satellites. The primary focus was on analyzing various modulation schemes and their application in the Starlink communication system.
High Speed Broadband Satellite Internet and Its Applications
Keywords: The development of satellite internet; GEO systems